Off-label reduced-dose apixaban does not reduce hemorrhagic risk in Taiwanese patients with nonvalvular atrial fibrillation: A retrospective, observational study. Issue 23 (11th June 2021) - Chen, I-Chih; Chang, Wei-Ting; Hsu, Po-Chao; Yeh, Ya-Lan; Zheng, Syuan; Huang, Yuan-Chi; Lin, Chih-Hsien; Tsai, Liang-Miin; Lin, Li-Jen; Liu, Ping-Yen; Liu, Yen-Wen
Abstract : Abstract: East Asians are reportedly at high risk of anticoagulant-related bleeding; therefore, some physicians prefer to prescribe low-dose direct oral anticoagulants (DOACs). Little is known about the therapeutic effectiveness and safety of off-label reduced-dose apixaban in East Asians with nonvalvular atrial fibrillation (AF). We aimed to investigate the effectiveness and safety of off-label reduced-dose apixaban in Taiwanese patients with nonvalvular AF. This retrospective cohort study enrolled 1073 patients with nonvalvular AF who took apixaban between July 2014 and October 2018 from 4 medical centers in southern Taiwan. The primary outcomes included thromboembolic events (stroke/transient ischemic attack or systemic embolism), major bleeding, and all-cause mortality. Among all patients, 826 (77%) patients were classified as the "per-label adequate-dose" treatment group (i.e., consistent with the Food and Drug Administration label recommendations) while 247 (23%) patients were the "off-label reduced-dose" treatment group. The mean follow-up period was 17.5 ± 13 months. The "off-label reduced-dose" group did not have a lower major bleeding rate than the "per-label adequate-dose" group (4.8% vs 3.8%, adjusted hazard ratio [HR] 1.20, 95% confidence interval [CI] 0.69–2.09), but had a nonsignificantly higher incidence of thromboembolic events (4.23% vs 3.05%, adjusted HR: 1.29, 95% CI: 0.71–2.34). An off-label reduced-dose apixaban treatment strategy may not provide incremental benefits or safety for Taiwanese patients with nonvalvular AF.